Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content: 1. Palestinian Administrative Investigation and Judicial Commissions in the Scale of Justice and Fairness / Palestine Al-Bireh Municipality Administrative Investigation Case study Dr. Ziyad Said Al-Taweel 2. International responsibility for breaching the principle of prohibition of the use or threat of force and the extent of its impact on contemporary international relations (A descriptive analytical study of the responsibility for the violations of the principle in the Russian aggression against Ukraine) Co-Prof. Abker Ali Abdelmagead 3. Estimating the degree of impact of courses and workshops provided by international organizations for workers in the Northwest Region waste dump (Al-Ekaider) on work from the perspective of workers and their suggestions for developing work Eng. Ashraf Saleh Mohammad Bani Hani 4. Protection of children’s rights in Omani legislation in the light of the rules of international law Mr. Abdul-Rahim Yahya Khalfan Al-Siyabi, Dr. Abdul-llah Amin 5. Public Expenditures and their Effects on Economic Stability "The ninth five-year plan in the Sultanate of Oman 2016-2020, an applied sample Dr. Musallam Salim Mohammed Al-Awaid 6. The legal status of the partner during the establishment of the Commercial Solidarity Company Co-Prof. Abdul-Razzaq Omar Jajan, Mr. Muhammed Qabil Al-Sulami 7. Implementation of the Electronic Document Management System in Joint Services Council for Irbid Governorate Mr. Malek Mohammed Kalil Aljamrh